Implementasi Reward dan Punishment dalam Meningkatkan Kedisiplinan Belajar Siswa di MTs Raudlatul Muta’alimin Sawahrejo Moropelang Babat Lamongan - Shokhibun Naja; Sulhatul Habibah; Siti Lathifatus Sun'iyah (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
The purpose of this study was to determine: 1) Implementation of Reward and punishment at MTs Raudlatul Muta'alimin Sawaharjo Moropelang Babat Lamongan. 2) Student discipline in the implementation of rewards and punishments at MTs Raudlatul Muta'alimin Sawaharjo Moropelang Babat Lamongan 3) Supporting and inhibiting factors for the implementation of rewards and punishments on student discipline at MTs Raudlatul Muta'alimin Sawaharjo Moropelang Babat Lamongan. This research uses qualitative research methods. The subject of this research is MTs Raudlatul Muta'alimin students. Data collection methods in this study are observation, interview and documentation methods. Data analysis techniques used in this study include data reduction, display, and conclusion. The results of this study can be seen that the implementation of Reward and Punishment in improving student learning discipline at MTs Raudlatul Muta'alimin can encourage students to behave disciplined. Rewards are given so that students are motivated to behave in a disciplined manner, Punishment is carried out to reduce rule violations in students. Reward and punishment applied by teachers make students have a disciplined character and behave positively, so that the learning outcomes obtained by students increase to achieve the expected results.